Motivated to Invest or Afraid to Risk? An Economic Study on Student Interest in the Sharia Capital Market in Kudus - Hidayat, Muhammad Rachmat; Sukardi, Agung Slamet (International Journal of Economics Development Research (IJEDR), 2025)
This study aims to analyze the influence of motivation and risk perception on investment interest in the sharia capital market, a case study on students in Kudus. The data collection technique used in this study was using a questionnaire distributed through google form to 100 students taken using the purposive sampling technique.  The population used in the study was the students of the Islam Negeri Kudus Institute of Religion and Muria Kudus University. The data analysis uses multiple linear regression. This study will explain how the motivation and perception of rirsirko affect interest in investing in the sharia capital market. The results of this study show that motivation and risk perception affect investment interest in the sharia capital market in students in Kudus.